Qana’ah sebagai Strategi Koping Religius Mahasantri Fresh Graduate yang Mengalami Stress Kerja - Zulaiha Rohwiyani Kharismawati; Vera Imanti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Fresh graduates often experience work-related stress due to professional demands, reality shock, and a lack of support from colleagues, which may lead to negative psychological responses. This study aims to explore the role of qana’ah as a specific form of religious coping strategy among fresh graduate mahasantri. This study uses a qualitative approach with purposive sampling technique. Data collection was conducted through semi-structured interviews, and to ensure data validity, triangulation of sources was used. The data analysis technique used was narrative analysis using the Clandinin & Connelly (1989) model. The findings indicate that qana’ah plays a significant role as a religious coping strategy for fresh graduate mahasantri in dealing with work-related stress through two main aspects: self-control as a form of self-regulation grounded in religious values, and self-acceptance developed through attitudes of patience (sabr) and reliance on God (tawakkal). In addition, social support from family and the surrounding social environment is crucial for fresh graduate mahasantri, as it serves as a fundamental foundation in fostering inner peace, emotional resilience, and the practice of qana’ah when facing pressures in the workplace.